Implementation of Circular Economy in Agribusiness SMEs and Its Impact on Business Sustainability: A Case Study - Riska Ariyanti; Popong Nurhayati; Asep Taryana (Newinera Publisher, 2025)
The circular economy has emerged as an important approach to enhancing agribusiness sustainability by shifting production systems from linear models toward regenerative processes that preserve resource value. This study identifies and evaluates the implementation of an integrated livestock farming system in agribusiness micro, small, and medium enterprises through a case study of CV Mitra Tani Farm, an integrated livestock-based enterprise in Indonesia. Circular agribusiness practices were identified using the 9R principles, and the analysis employed the Triple Bottom Line framework to assess sustainability performance across economic, environmental, and social dimensions. The identification results indicate that the integrated farming system implemented at MT Farm operationally reflects the core principles of the circular economy. The evaluation further shows that circular practices such as waste-to-resource conversion, integrated farming systems, and product diversification effectively reduce operational waste, improve resource efficiency, and maintain ecological balance. Socially, these practices promote employment creation, partner capacity building, and the strengthening of rural collaboration. From an economic perspective, circular practices enhance business resilience; however, the economic potential of waste-based activities has not yet been fully optimized, indicating the need for further development to enable the circular economy to play a more effective role in supporting the transformation toward sustainable agribusiness.